THE OSWALDO CRUZ INSTITUTE MOLLUSK COLLECTION: IMPROVEMENTS ON DIVERSITY AND INFRASTRUCTURE OVER THE LAST YEARS - Gomes, Suzete Rodrigues; Fernandez, Monica Ammon; da Silva, Elizangela Feitosa; da Costa Lima, Alessandra; Thiengo, Silvana Carvalho (Arquivos de Ciências do Mar, 2017)
This study aimed at analyzing the Oswaldo Cruz Institute Mollusk Collection (CMIOC) database in relation to the diversity of families and geographic distribution of the lots, as well as to divulge the improvements on infrastructure over the last years. Currently, CMIOC includes 10,102 lots of freshwater (17 families; including syntypes and topotypes) and terrestrial gastropods (23 families), and bivalves. Planorbidae is the most representative family (6,330 lots), while Biomphalaria straminea, the most sampled species (1,084 lots), followed by B. glabrata (612 lots), and B. tenagophila (581 lots). The second most representative family is Ampullariidae (1,255 lots). Although, terrestrial gastropods include only 181 lots, they represent 23 families, being Subulinidae (59 lots), Bulimulidae (16 lots), and Succineidae (24 lots) the most well represented. A total of 61 countries are represented on CMIOC. It includes mainly specimens from Brazil (8,760 lots), representing all 26 Brazilian States plus the Federal District, especially from the Rio de Janeiro State, with samples from all its 92 municipalities (1,647 lots). Improvements on infrastructure include new rooms, cabinets, equipment, and staff, which have been possible thanks to institutional and external financial support. CMIOC has been notoriously playing an important role for different malacological studies on public health and biodiversity, having a great potential to expand and contribute in many other areas of knowledge.